اختلافِ مرویات اور اس کے تفسیرِ قرآن پر اثرات: تفسیری روایت کا تحقیقی و تنقیدی مطالعہ: VARIANT NARRATIONS AND THEIR IMPACT ON THE INTERPRETATION OF THE QUR’AN: AN ANALYTICAL AND CRITICAL STUDY OF THE EXEGETICAL TRADITION (Al-Aasar, 2025)
The interpretation of the Qur’an has historically relied upon transmitted reports including Prophetic traditions, statements of the Companions, and narrations from the Successors. However, the presence of variant narrations (Ikhtilaf al-Marwiyat) within the exegetical tradition has led to differences in understanding certain Qur’anic passages. This study explores the nature, causes, and impact of variant narrations on Qur’anic exegesis. By examining classical tafsir literature and analyzing the methodologies of major exegetes, the research highlights how these variations influence theological doctrines, legal rulings, and socio-ethical interpretations. The paper adopts a qualitative analytical approach and relies on classical tafsir works such as those of Muhammad ibn Jarir al-Tabari, Ismail ibn Kathir, Abu Abdullah al-Qurtubi, and Fakhr al-Din al-Razi. The study concludes that the diversity of narrations does not weaken the authority of Qur’anic interpretation but rather enriches the intellectual and scholarly heritage of Islamic scholarship. The phenomenon of اختلافِ مرویات (variant narrations) has long been a central subject in the discipline of Qur’anic exegesis, significantly influencing interpretive diversity among classical and contemporary scholars. This study critically examines the nature, causes, and classifications of اختلاف مرویات and explores its profound impact on the interpretation of the Qur’an within the framework of تفسیری روایت (exegetical tradition).The research adopts an analytical and comparative methodology to investigate how differences in transmitted reports particularly those related to prophetic traditions (Hadith), sayings of the Companions (Athar), and early exegetical authorities have contributed to multiple interpretive possibilities. It highlights that اختلاف مرویات arises due to various factors, including differences in chains of transmission (Isnad), textual variations (Matn), contextual understanding, linguistic diversity, and methodological preferences among exegetes.Furthermore, the study demonstrates that these variations have significantly influenced theological interpretations, legal rulings, and socio-ethical applications derived from the Qur’an. While some differences lead to apparent contradictions, many are reconcilable through اصولِ تفسیر (principles of exegesis), such as tarjih (preference), tatbiq (reconciliation), and tafsir al-Qur’an bil-Qur’an. The research also underscores the role of Hadith criticism and principles of authentication in determining the reliability of narrations and their suitability for exegetical use.Importantly, the paper argues that اختلاف مرویات should not be viewed merely as a source of confusion, but rather as a reflection of the richness, depth, and intellectual dynamism of the Islamic scholarly tradition. It contributes to a broader understanding of how exegetical plurality can coexist with interpretive coherence when guided by sound methodological principles.The study concludes by emphasizing the need for a balanced and critical approach in contemporary Qur’anic studies one that appreciates classical scholarship while applying rigorous analytical tools to navigate differences in narrations. This approach can enhance both academic research and practical engagement with the Qur’an in modern contexts.